The innocent behind the scandal - Green, Abby (Green, Abby. Marchetti dynasty, 2020)
From London to St Petersburg ... Everyone is talking about this couple! Photographer Zoe Collins is ready to be awakened at the hands of charismatic billionaire Maks Marchetti. She's been hurt one too many times and is determined to protect her heart, but she's done with protecting her virginity! Maks has never met anyone that intrigues him like Zoe. Orphaned and innocent, yet she seems almost as cynical about love as he is. A fact which makes their nights together dangerously addictive. But can a bond forged in the bedroom withstand an expose in the headlines?